A description on multiple intelligences employed by diploma students in UiTM Sarawak / Saira Joe ... [et al.] - Joe, Saira; Alfred Tom, Amelia; Sandai, Rosline (2011)
Each proficiency course in UiTM Sarawak has a standardised syllabus as well as utilises the same teaching and learning materials. However, it has been noted that diploma students from different faculties in the university would perform differently in their English proficiency courses. In this endeavour to achieve higher academic standards and student success, we seem to have forgotten an important piece for solving the academic puzzle. That piece is how students learn and the relationship of intelligence to the learning process. In relation to this, Teele (2000) clearly stated that all students can learn and succeed but not in the same way and not on the same day.